PENINGKATAN TEKNOLOGI PRODUKSI DAN DIGITALISASI PEMASARAN USAHA PENGOLAHAN GABAH PADA BUMDES - Utan Sahiro Ritonga; Reshi Wahyuni; Citra Defira (Universitas Mataram, 2025)
Most rice milling businesses in rural areas are operated with limited technological knowledge, resulting in rice production that does not meet market needs. On the other hand, changes in consumer behavior toward online transaction systems require village businesses to adapt and increase their digital capacity. Therefore, increasing the technical capacity of BUMDes administrators and members through training in rice processing and the implementation of digital marketing is becoming increasingly important. Implementation methods include structured counseling and training. The presentation of activity results is descriptive and quantitative based on pretest and posttest results, which consist of production aspects including determining the appropriate level of dryness of rice, sorting and cleaning activities, polishing and rice appearance, and storage techniques. The digital marketing aspect includes marketing digitalization competencies, online store creation, testimonial content creation, and informative content. The results of the activity, which was measured from 26 BUMDes administrators and members, showed significant progressive improvements in all indicators, especially the ability to determine water content (17.86%), sorting (14.29%), and polishing (10.71%). The digitalization aspect saw the highest achievement percentage in the online store profile indicator (96.15%), with the highest progressive increase in informative content (42.31%). These results indicate that the empowerment activities successfully improved the technical skills and digital literacy of participants, although strengthening of testimonial content management is still needed. Overall, the designed program plays a significant role in driving the transformation of Serdang Indah BUMDes into a village economic institution that is adaptive to technological developments and able to compete in the ever-growing digital market.